Antagonistic Activity of Agaricuscampestris mushroom Extracts Against some Human Pathogenic Bacterial Species - Shafiq, Shatha Ali; Sahib, Rasha Salam (Asian Journal of Pharmaceutical Research and Development, 2022)
The present study focused on the evaluation of Agaricuscampestris mushroom extracts activity against four clinical isolates Escherichia coli; Pseudomonas aerginosa; Staphylococcus haemolyticus and Staphylococcus aureus. Agaricuscampestris mushroom extracts varied in their antimicrobial activity. The intensity of the antimicrobial effect is dependent upon the solvent , concentration of the mushroom extract and the organism being tested against .Therefore, The hot water and ethanolic extract 96%showed maximum inhibition at high concentrations specially at 500 mg/ml concentration( 17, 16, 19, 16 ) mm and ( 20,21,19,20) against E. coli , Pseudomonas aerginosa; Staphylococcus aureus and Staphylococcus haemolyticus respectively compared with methanolic extract . The ethyl acetate extract of the powder mushroom of Agaricuscampestris was analyzed to 9 chemical compounds belonged to fatty acids and their derivatives and included :-Nonadecane, Pentacosane, Octadecane, Heptadecane, Heneicosane, Hexadecane, 2,6,10,14-tetramethyl, Butanoic acid, 3,7-dimethyl-6-octenyl ester, Phthalic acid mono-2-ethylhexyl ester , Octanoic acid, heptadecyl ester.